The Value of Color Duplex Sonography in the Discrimination of Benign and Malign Breast Masses - Murat, Ayşe; Arslan, Anıl; Oğur, Erkin (Fırat University, 2005)
Objectives: In our study, we aimed to investigate the value of color duplex sonography (CDUS) in the discrimination of benign and malign breast masses. Materials and Methods: A total of 53 patients aged 26-69 years who had breast masses in their mammography and/or ultrasound, were enrolled in the study. The presence of vascularity within the mass, localization of the vascular structures and the type of flow were determined with CDUS. In the patients who had flow, resistive index (RI) and pulsatility index (PI) values were measured. Histopathologic results of the masses were obtained with biopsies or operation results. Results: In 28 of 31 patients (90.3%) who were suggested to have malign breast masses in their mammography and/or ultrasonography and subsequently supported histopathologically, vascularity was provided from the mass in the CDUS. The range of RI and PI values varied between 0.57 and 1.00 (mean value of RI: 0.74) and between 0.90 and 3.17 (mean value of PI: 1.48) respectively. In 11 of 22 (50%) breast masses which were found to be benign histologically, flow was present within these masses. RI values were between 0.50 and 0.86 (mean value of RI: 0.65), PI values were between 0.67 and 2.43 (mean value of PI: 1.10). Conclusion: Arterial flow within the mass was detected in more patients with malign breast masses compared to the patients with benign masses. Significant difference was found between RI and PI values of the two groups. RI and PI values were increased in the malign group. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Çalışmamızda, renkli dupleks ultrasonografinin (RDUS) benign ve malign meme kitlelerinin ayırımındaki yerini incelemeyi amaçladık. Gereç ve Yöntem: Mammografilerinde ve/veya ultrasonografilerinde meme kitlesi saptanan, yaşları 26 ile 69 arasında değişen toplam 53 olgu çalışmaya alındı. RDUS ile kitle içerisindeki vaskülarite varlığı, vasküler yapıların lokalizasyonu ve akım türü belirlendi. Arteriyal akım saptanan olgularda, rezistif indeks (RI) ve pulsatilite indeks (PI) değerleri ölçüldü. Kitlelerin histopatolojik sonuçları aspirasyon-eksizyonel biyopsilerle veya operasyon sonuçlarıyla elde edildi. Bulgular: Mammografi ve/veya ultrasonografi bulgularına göre malign meme kitlesi olduğu düşünülen ve histopatolojisi ile desteklenen 31 olgunun 28'inde (%90.3) RDUS'da kitleden vasküler akım alındı. RI değerleri 0.57 ile 1.00 arasındaydı (ortalama RI: 0.74). PI değerleri 0.90 ile 3.17 arasındaydı (ortalama PI: 1.48). Histopatolojisi benign olarak tespit edilen 22 meme kitlesinin 11'inde (% 50) akım mevcuttu. RI değerleri 0.50 ile 0.86 (ortalama RI: 0.65), PI değerleri 0.67 ile 2.43 (ortalama PI: 1.10 ) arasındaydı. Sonuç: Malign meme kitlelerinde benignlere göre daha yüksek oranda arteriyal akım saptandı. Her iki grup arasındaki RI ve PI değerlerinde anlamlı fark tespit edildi. RI ve PI değerleri malign grupta artmıştı. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Benign ve Malign Meme Kitlelerinin Ayırımında Renkli Dupleks Ultrasonografinin Yeri